A STUDY ON THE IMPACT OF JOB CHARACTERISTICS ON KEY ATTITUDES OF FACULTY MEMBERS IN PROFESSIONAL EDUCATIONAL INSTITUTES - Malik, Bhavna; Narang, Daviender (European Scientific Journal, ESJ, 2015)
The purpose of this study is to investigate the impact of job characteristics on key attitudes (job satisfaction and organizational commitment) of faculty members in professional educational institutes in Delhi region. In addition, the study explored the satisfaction level and commitment level of faculty members with different dimensions of their job. A survey of 251 faculty members working in private professional educational institutes was conducted. Several analytical techniques such as Pearson correlation and Hierarchical regression were used to evaluate the relationship among variables. The findings of the study indicated that job characteristics promotional opportunities, task variety, pay satisfaction, and professional development, resulted in a high affective commitment, while participation in decision making was related to normative commitment. Promotional opportunity, pay, and participation were highly related with the job satisfaction of the faculty members.